2011
DOI: 10.1128/aem.00583-11
|View full text |Cite
|
Sign up to set email alerts
|

Calicivirus Removal in a Membrane Bioreactor Wastewater Treatment Plant

Abstract: To evaluate membrane bioreactor wastewater treatment virus removal, a study was conducted in southwest France. Samples collected from plant influent, an aeration basin, membrane effluent, solid sludge, and effluent biweekly from October 2009 to June 2010 were analyzed for calicivirus (norovirus and sapovirus) by real-time reverse transcription-PCR (RT-PCR) using extraction controls to perform quantification. Adenovirus and Escherichia coli also were analyzed to compare removal efficiencies. In the influent, sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 46 publications
6
56
1
Order By: Relevance
“…Our inference model results estimated that NoV GI and NoV GII influent concentrations were higher from January to May than from June to November, which is consistent with other specific reports in the literature (25,26,53). As an example, Katayama et al (26) reported NoV influent concentrations to be more abundant in winter than in summer, which is consistent with the present model results (Ϯ1 log 10 ; Fig.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our inference model results estimated that NoV GI and NoV GII influent concentrations were higher from January to May than from June to November, which is consistent with other specific reports in the literature (25,26,53). As an example, Katayama et al (26) reported NoV influent concentrations to be more abundant in winter than in summer, which is consistent with the present model results (Ϯ1 log 10 ; Fig.…”
Section: Discussionsupporting
confidence: 83%
“…In the peer-reviewed scientific literature, evaluations of log 10 reductions are usually performed by assigning a value (e.g., 0 or LOD [27,61] or one-half the LOD or an arbitrary value [52]) to measurements below the LOD, by ignoring those values (25), or by providing only a lower limit of the actual log 10 reduction (e.g., a log 10 reduction of ՅϪ3.8 [53]). Ignoring censored data or replacing these observations with a given value biases the inference process (62,63).…”
Section: Discussionmentioning
confidence: 99%
“…Ottoson et al [21] note that the presence of indicator organisms does not always indicate the presence of pathogens. Conversely, it has been suggested that much of the controversy with regards to indicator and pathogen correlations is the result of studies with insufficient data for assessing correlations [56,126] and these problems can be rectified by taking the appropriate quality control measures. On the other hand, Sima et al [56] pointed out potential pitfalls of the RT-PCR method of quantifying virus genomes due to compounds present in wastewater samples, which may interfere with extraction efficiencies, and raised the importance of careful quality control measures also in this respect.…”
Section: Quantification Methods and Indicator-pathogen Correlationmentioning
confidence: 99%
“…On the other hand, because viruses tend to attach to solid surfaces, most viruses that survive wastewater treatment are likely associated with waste-activated sludge and may be present in biosolids [14,56,104]. This warrants safe disposal of potentially pathogen-containing biosolids.…”
Section: Relative Contributions Of Biomass Processes and Membrane Rejmentioning
confidence: 99%
“…However, no significant differences in NoV reduction between UV disinfection and UV disinfection plus TiO 2 treatment were found in one study (71). Membrane bioreactor technology, which combines biological-activated sludge processes and membrane filtration, has been reported to remove NoV (GI and GII) at levels ranging from 3.3 to 6.8 log 10 units (72,73).…”
Section: Contamination Sourcesmentioning
confidence: 99%